Penyuluhan dan Deteksi Dini Stunting sebagai Upaya Pencegahan Stunting pada Balita - Dewi Zolekhah; Liberty Barokah; Yuni Very Anto (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
This community service is themed "Counseling and Early Detection of Stunting as an Effort to Prevent Stunting in Toddlers". The purpose of this community service is expected that mothers who have babies can learn about Early Detection of Stunting as an Effort to Prevent Stunting in Toddlers. Stunting is a major public health problem related to nutrition globally, especially in most developing countries including Indonesia. The prevalence of stunted toddlers in Indonesia reaches 21.6% with 16 provinces still below the average stunting rate in Indonesia, one of which is Aceh at 31.2%. Stunting creates obstacles in the formation, growth and development of organs in the short term which can cause death, morbidity or disability. Furthermore, in the long term, stunting has a negative impact on the size of a person's body as an adult, intellectual ability, economic productivity, reproductive ability, diseases related to metabolism and blood vessels. Toddlers with stunting have a fourfold risk of experiencing respiratory tract infections. This community service will be carried out offline and integrated into the Neonatal Care for Babies, Toddlers and Children course. The target of this service is: Mothers who have babies and toddlers. The expected output from the implementation of this community service is the publication of scientific journals. The implementation of this activity is planned in three stages, namely preparation, implementation, and the final stage. The preparation stage includes a series of activities from problem assessment and preparation of proposals. The implementation stage of the activity is to provide Health Education related to early detection of stunting. The preparation stage is carried out by preparing a report based on the activities that have been carried out.